Shielding working memory from distraction is more effortful than flexible updating - Danae Papadopetraki; Monja I. Froböse; Andrew Westbrook; Bram B. Zandbelt; Roshan Cools (Scientific Reports)
Abstract Exerting cognitive control is known to carry a subjective effort cost and people are generally biased to avoid it. Recent theorizing suggests that the cost of cognitive effort serves as a motivational signal to bias people away from excessive focusing and towards more cognitive flexibility. We asked whether the effort cost of stable distractor resistance is higher than that of non-selective flexible updating of working memory representations. We tested this prediction by using (1) a delayed response paradigm in which we manipulate demands for distractor resistance and flexible updating, as well as (2) a subsequent cognitive effort discounting paradigm that allows us to quantify subjective effort costs. We demonstrate, in two different samples (28 and 62 participants) that participants discount tasks both high in distractor resistance and flexible updating when comparing with taking a break. As predicted, when directly contrasting distractor resistance and non-selective flexible updating the subjective cost of performing a task requiring distractor resistance is higher than that requiring flexible updating.